HUBUNGAN KARAKTERISTIK PENDERITA DENGAN KEJADIAN DEMAM TIFOID PADA PASIEN RAWAT INAP DI RSUD SALEWANGAN MAROS - Muh Zul Azhri Rustam (STRADA : Jurnal Ilmiah Kesehatan, 2012)
Introduction. Typhoid fever is an acute infectious disease of the small intestine. In Asia gained 17 million people with typhoid fever, and was found in every year there are 0.6 million deaths, or as much as 75-80% morbidity or mortality from the disease. Patients with typhoid fever in Indonesia is pretty much in the estimate 800/100.000 population per year, were found almost throughout the year, but especially in the summer. Objective. To determine the relationship of patient characteristics with the incidence of typhoid fever in hospitalized patients at the General Hospital in Salewangan Maros. Methods This type of research is survey research used an analytic approach to Cross Sectional Study. Sampling is being done with the technique of “total Sampling” noting that it going to take that all in-patients in hospitals Salewangan Maros in the period January-december 2010 with a number of 362 patients. Result. The results showed that age, sex, educational the status, and have a relationship with the incidence of typhoid fever with p value 0.000> 0.05 whereas employment the status no association with the incidence of typhoid fever with p value 0.707> 0.05 level. Conclusion. morbidity and mortality of typhoid fever can affect any age group, it should be done early prevention by immunization or vaccination where it can prevent the entry of germs and breed. Giving this information may include pamphlets, brochures, and banners, need to instill healthy behaviors that are not easilycontaminated by salmonella bacteria thypi.